Modelling quantum photonics on a quantum computer - Vetlugin, Anton N. (2022)
Modelling of photonic devices traditionally involves solving the equations of light-matter interaction and light propagation, and it is restrained by their applicability. Here we demonstrate an alternative modelling methodology by creating a "quantum copy" of the optical device in the quantum computer. As an illustration, we simulate quantum interference of light on a thin absorbing film. Such interference can lead to either perfect absorption or total transmission of light through the film, the phenomena attracting attention for data processing applications in classical and quantum information networks. We map behaviour of the photon in the quantum interference experiment to the evolution of a quantum state of transmon, a superconducting charge qubit of the IBM quantum computer. Details of the real optical experiment are flawlessly reproduced on the quantum computer. We argue that superiority of the "quantum copy" methodology shall be apparent in modelling complex multi-photon optical phenomena and devices.